Critical Dependence of Butterflies on a Non-native Host Plant in the Urban Tropics - Jain, Anuj; Zeng, Yiwen; Webb, Edward L. (Frontiers in Ecology and Evolution, 2021)
Increasing urbanization in the tropics has led to the loss of natural habitats and local extirpations and the introduction of non-native plants in urban centers. Non-native plants can have widespread positive and negative ecological implications on native fauna including butterflies. In the small tropical urbanized city-state of Singapore, Aristolochia jackii (Aristolochiaceae), a native host plant of the nationally threatened Common Birdwing (Troides helena) and Common Rose (Pachliopta aristolochiae), is considered extirpated, but their shared non-native host plant Aristolochia acuminata is a cultivated ornamental in urban habitat. We conducted systematic surveys from years 2010 – 2014 and collated sighting records from 1999 – 2019 to map the distribution of T. helena and P. aristolochiae, and their host plant A. acuminata. We utilized machine learning models (i.e. random forest algorithms) to establish the relationships between various habitat (managed and natural tree cover, waterbody and impervious surface cover) and life-history parameters (minimum distance from the nearest larval host plant and population source derived from expert knowledge) that are associated with the butterfly distributions. Response curves were generated for each species and projected spatially across Singapore’s landscape to estimate potential occupancy. We found that both butterflies had clustered distributions with a greatly reduced probability of occurrence further away from identified population sources and non-native A. acuminata. Both study species had similar spatial niche and similar species occurrence responses though there were differences in habitat preferences and temporal niche. Both species showed positive dependence on managed tree cover (Rose more than Birdwing) but the Birdwing also had high positive dependence on natural tree cover, unlike the Rose. We report novel findings that a non-native host plant can provide positive ecological benefits and critically sustain tropical butterfly populations. While there will be a need to evaluate the full ecological impacts of non-native plantings, we suggest using them as a secondary strategy when re-establishment of the native plants has failed particularly in highly urbanized tropical landscapes.